Effect of Bunch Removal on Grape Composition and Wine Quality of Vitis vinifera L. cv. Chardonnay - van Schalkwyk, D.; Hunter, J.J.; Venter, J.J. (South African Journal of Enology and Viticulture, 2017)
To determine whether grape composition and wine quality of premium wine grape cultivars in South Africa would be improved when certain degrees of bunch removal are applied at a later stage than 14°B and when all treatments are harvested at approximately the same sugar content, one-third and two-thirds of the bunches of Chardonnay were removed at l 7°B and 19°B in a field trial at Robertson for three consecutive seasons (1990 - 1993). In addition to these four treatments, a control treatment (no bunch removal) and a treatment where bunches were harvested on the sunny and shaded sides of the same canopy (without prior bunch removal) at approximately 21,5°B were also included in the study. The economic use of removed grapes was determined, whereas all factors, including additional labour costs, were taken into account to establish whether bunch removal is an economically viable practice. A maximum reduction in yield of 11,6 t ha-' compared to that of the control was obtained when two-thirds of the bunches were removed at 19°B. No measurable compensation in berry mass occurred when bunches were removed at l7°B and 19°B.  Grapes removed at 17°B and 19°B were suitable for the making of distilled and sparkling wine or for use in wine blends and thus contributed to the total income of the vineyard. Bunch removal did not improve must and wine composition. Few differences in the concentrations of individual sugar and organic acids in the grapes, and volatile acid, alcohol and ester compounds in the wines were obtained. Wine of treatments where bunches were removed tended to be of lower quality. No improvement in wine quality was found with differential harvesting on the sunny and shaded sides of the canopy. Bunch removal was labour intensive and not economically viable.